(untitled) (MMIT Proceedings, 2026)
Sustainable development is considered one of the most important global challenges for countries in the twenty-first century. The European Union, through its adopted climate policies and circular economy strategies, is a global actor in sustainable development. Uzbekistan, in this context, has accelerated its sustainability and green transition policy reforms following the economic liberalization and institutional modernization efforts it initiated in recent years. This study comparatively examines the current practices in the European Union and Uzbekistan in accordance with the principles of sustainable development in general. The research results show that the EU has stronger legislation, financial instruments, and a more developed and institutionalized sustainability policy. The European Green Deal and the zero-carbon emission targets adopted within this framework demonstrate the EU’s long-term sustainability vision. In contrast, it has been understood that Uzbekistan is in a transition phase in terms of these policies, but has made significant progress through renewable energy investments and international cooperation with its "Green Economy Transition Strategy 2019–2030". However, certain corporate obstacles, financial problems, and technological dependency continue to hinder Uzbekistan’s sustainability transformation. A comparative analysis of the EU and Uzbekistan’s sustainable development policies reveals that while the EU prioritizes comprehensive net-zero emissions and regulatory measures, Uzbekistan prioritizes economic development and modernization, as well as phased environmental reforms. The study results indicate that Uzbekistan can significantly benefit from the EU’s experience in sustainable finance and environmental management. Strengthening international cooperation between the EU and Uzbekistan could facilitate Uzbekistan’s inclusion of green investments and the successful implementation of sustainable development principles. In conclusion, sustainable development contributes not only to the implementation of protective environmental policies but also to strengthening institutional structures and ensuring inclusive economic and social transformation based on international cooperation.